2019
DOI: 10.1002/sdtp.13336
|View full text |Cite
|
Sign up to set email alerts
|

P‐179: Optics of Curved OLEDs

Abstract: Although flexible OLEDs are often used in curved formats and their optics would differ from planar OLEDs, their impacts on OLED emission characteristics are not carefully studied before. Here we investigate optics of curved OLEDs by both optical simulation and experiments and reveal their implications to real flexible OLED applications. We demonstrate light extraction efficiency can be substantially enhanced, or emission profile and viewing angles can be varied, with curved OLEDs in some formats. This may be o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In our previous study [1], we showed that in a curved OLED, because the tangential plane of the emitting point, PA, is not parallel to the tangential plane on the light exit surface, PB (between the substrate/superstrate and the air as illustrated in Figure. 2), the initial emission angle, θ1, would not equal to the incident angle, θ2, on PB and hence the effective critical angle, θc,eff (i.e., escape cone), seen by the original emitter would differ from the critical angle, θc, in the planar structure. In spherical convex or cylindrical convex structures as in Figure. 2, θc,eff would be larger than θc, possibly resulting in significant enhancement in light out-coupling with appropriate designs (i.e., >90% substrate-to-air extraction efficiency).…”
Section: Objective and Backgroundmentioning
confidence: 98%
“…In our previous study [1], we showed that in a curved OLED, because the tangential plane of the emitting point, PA, is not parallel to the tangential plane on the light exit surface, PB (between the substrate/superstrate and the air as illustrated in Figure. 2), the initial emission angle, θ1, would not equal to the incident angle, θ2, on PB and hence the effective critical angle, θc,eff (i.e., escape cone), seen by the original emitter would differ from the critical angle, θc, in the planar structure. In spherical convex or cylindrical convex structures as in Figure. 2, θc,eff would be larger than θc, possibly resulting in significant enhancement in light out-coupling with appropriate designs (i.e., >90% substrate-to-air extraction efficiency).…”
Section: Objective and Backgroundmentioning
confidence: 98%
“…A cylindrical shape is the first order, and a spherical shape is the second order of the curvatures. Each of them can be the outer or inner surface light emission source 18 . Planar and cylindrically curved LSs are partially and schematically shown in Figure 3.…”
Section: Oled and Bending Issuesmentioning
confidence: 99%